2014
DOI: 10.1002/elps.201300261
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cerebrospinal fluid γ‐aminobutyric acid by capillary electrophoresis with laser‐induced fluorescence detection

Abstract: The measurement of γ-aminobutyric acid (GABA) is suitable for investigating various neurological disorders. In this study, a sensitive and selective method for free GABA quantification in cerebrospinal fluid (CSF) has been standardised. This method is based on CE with LIF detection using 4-fluoro-7-nitrobenzo-2-oxa-1,3-diazole (NBD-F) as a derivatisating agent. The reaction conditions (NBD-F concentration, pH, temperature and reaction time) and the electrophoretic parameters (run buffer composition and pH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…A key finding of the present study was that neonates displayed significantly lower in vivo brain GABA+ levels than children in both the BG and cerebellum. Previous ex vivo studies of postmortem brains and cerebrospinal fluid also reported significant increases in GABA concentrations with age . Therefore, it is likely that in vivo GABA concentrations in the BG and cerebellum are lower in neonates compared with children, and that they increase with development.…”
Section: Resultsmentioning
confidence: 95%
“…A key finding of the present study was that neonates displayed significantly lower in vivo brain GABA+ levels than children in both the BG and cerebellum. Previous ex vivo studies of postmortem brains and cerebrospinal fluid also reported significant increases in GABA concentrations with age . Therefore, it is likely that in vivo GABA concentrations in the BG and cerebellum are lower in neonates compared with children, and that they increase with development.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, we know that a subset of patients with SSADHD has a more severe phenotype, featuring adult-onset epilepsy (Parviz et al 2014), and there have been instances of SUDEP (sudden unexplained death in epilepsy) in adulthood (Lapalme-Remis et al 2015; Knerr et al 2010; Gibson and Pearl, unpublished observation). Previously, Casado and coworkers (2014) documented that GABA levels in cerebrospinal fluid from 55 pediatric controls showed a progressive increase with age. Unfortunately, we could not assess this age-related parameter in our control cohort since information on age characteristics was limited.…”
Section: Discussionmentioning
confidence: 97%
“…Patient age range was 5–41 years (median, 8 years), and ages were available for all. Clinical details were not available on patients at the time of sample shipment, and to our knowledge none of the patients was concurrently receiving vigabatrin or other antiepileptic which may have artefactually elevated plasma total GABA, as is the case for GABA in cerebrospinal fluid for patients receiving vigabatrin (Gibson et al 1995; Casado et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…7,8 Our aim was to analyse the CSF free-GABA values in a large cohort of patients with different neuropaediatric disorders, by assessing clinical, biochemical, and molecular data. Although there are a few reports on small groups of patients, they emphasize only the influence of antiepileptic drugs (AEDs) and mainly focus on patients with epilepsy.…”
Section: Aedmentioning
confidence: 99%
“…7,8 Our aim was to analyse the CSF free-GABA values in a large cohort of patients with different neuropaediatric disorders, by assessing clinical, biochemical, and molecular data. …”
mentioning
confidence: 99%